2000-ЖЫЛЛАРДАҒЫ ҚАРАҚАЛПАҚ РОМАНЫ: ТАРИЙХЫЙ ДӘРЕК ҲӘМ ЖАЗЫЎШЫНЫҢ КѲРКЕМ ҚЫЯЛЫ - Нуржанов, П. (FAN va JAMIYAT, 2022)
The article analyzes the problem of the Karakalpak historical novel of the 2000s and the uniqueness of the creation of the hero’s image on the example of K. Karimov’s work "Darvish".